TINGKAT KECEMASAN DAN POST POWER SYNDROME PADA LANSIA PENSIUNAN APARATUR SIPIL NEGARA (ASN) - Kamsari, Kamsari; Hikmawati, Kitri; Riyanto, Riyanto; Jerli Marsanda, Liviana (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Many people believe that retirement marks the beginning of a decline in their quality of life. Many individuals experience anxiety because they cannot imagine their post-retirement life. This can lead to depression and psychological shock as well as very severe anxiety for those who cannot accept their condition or suffer from post power syndrome. Objektive: This study aims to determine whether there is a relationship between anxiety levels and Post Power Syndrome in the Elderly. Method: This study is a quantitative study using a descriptive analytical method with a cross-sectional approach. The sampling technique used a total sampling of 53 respondents. The instruments used were the Hamilton Anxiety Rating Scale (HARS) questionnaire to assess anxiety levels and the post power syndrome questionnaire to assess post power syndrome levels. The analysis used in this study was a bivariate analysis using the Chi Square test. Results: The study found that the anxiety levels of 53 respondents ranged from severe to very severe anxiety as many as 18 (34.0%) and moderate levels of post power syndrome as many as 33 (62.3%). The results of the bivariate analysis P-value = 0.000 (α <0.05). Conclusion: so it can be concluded that Ha is accepted, which means there is a relationship between anxiety levels and post-power syndrome in elderly retired civil servants (ASN) in Lemah Mekar Village, Indramayu.